How Close the Aid-Community and ECA Universes Are - Ferdinand Schipfer (Global Policy, 2019)
While backgrounds and motives of Export Credit Agencies and Development Institutions may differ, the countries, projects and objectives they are working on are very often the same. This calls for much more and better coordinated co-operation.
Keywords: 320